Chrysophanol, physcion, hesperidin and curcumin modulate the gene expression of pro-inflammatory mediators induced by LPS in HepG2: in silico and molecular studies - Selim, Nabil; Sobeh, Mansour (Antioxidants, 2019)
Hepatitis is an inflammatory condition that can develop hepatocellular carcinoma. Traditional medicine has always been the pillar of medical practice. However, it became less compatible with the current understanding of the diseases and the possible treatment. Therefore, in silico tools could be utilized for building the bridge between the legacy of the past and the current medical approaches allowing access to new therapeutic discoveries. In this work, a Chinese traditional medicine database was screened using structure-based virtual screening to identify molecules that could inhibit p38 alpha mitogen-activated protein kinase (MAPK). Out of the identified compounds, four selected compounds: chrysophanol, physcion, curcumin and hesperidin were isolated from their respective sources and their structures were confirmed by spectroscopic methods. These compounds decreased the gene expression of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and interleukin-1beta (IL-1β) in lipopolysaccharide (LPS) induced inflammation in a hepatocellular carcinoma cell line (HepG2) in a dose-dependent manner. The molecular docking study revealed the specificity of these compounds towards p38 MAPK rather than other MAPKs. In conclusion, the molecular and in silico studies suggest that the isolated compounds could be a potential treatment for hepatitis by resolving inflammation controlled by MAPKs, thus limiting the development of further complications and lower side effects.
Gesehen am 31.10.2019